Red cell indices and formulas used in differentiation of β-thalassemia trait from iron deficiency in Thai Adults - Soontharee Plengsuree (2018)
© 2015 Informa Healthcare USA, Inc. β-Thalassemia (β-thal) and iron deficiency cause most microcytic anemias. Red cell indices and formulas have been established as simple, fast, and inexpensive in discrimination between these two hematological disorders in school children. However, whether these formulas could be applied to diagnose β-thal trait and iron deficiency in adult Thai subjects is unclear. The aim of this study was to examine the diagnostic accuracy of five red cell indices [red blood cell (RBC) counts, mean corpuscular volume (MCV), mean corpuscular hemoglobin (Hb) (MCH), mean corpuscular Hb concentration (MCHC), and red cell distribution width (RDW)] and nine formulas (RDW/RBC, RDW Index, Sirdah, Green and King, Mentzer, England and Fraser, Ehsani, Srivastava and Shine and Lal). Their sensitivity, specificity, positive predictive value (PPV), and negative predictive values (NPV), efficiency, and Youdens Index were analyzed in 102 β-thal trait and 64 iron deficiency adult Thai subjects. The RDW/RBC formula proved to be the most reliable index as they had 100.0% specificity and PPV and the highest efficiency (94.58%) and Youdens Index (91.18%), as well as high sensitivity (91.18%) and NPV (87.67%). Therefore, this formula could be used in initial discrimination of β-thal trait from iron deficiency in adult Thai subjects.